2022
DOI: 10.3390/nano12030578
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Impact of the Washing Steps of Layered Double Hydroxides (LDH) on the Electrochemical Performance

Abstract: The washing of layered double hydroxides (LDH) material is mostly purposed to discard the unreacted products after the reaction has been completed. However, this study demonstrated that the washing stage can also be targeted to optimise the electrochemical performance of LDH by using an appropriate solvent. Solvents, namely, ethanol, acetone, and an ethanol–acetone solution (2:1) were used for the washing of LDH and the impacts thereof on the structural, physical, chemical, morphological, and electrochemical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…The crystalline structure is an important part for LDH materials. It was reported that during the charging step, the surface of LDH materials is not the only part that participates, the entire crystalline structure is also involved via intercalation/de-intercalation of electrolyte ions; promoting the excellent energy storage capabilities of LDH materials [ 6 , 30 , 31 , 32 , 33 ]. Therefore, the LDH crystalline domain deserves attention.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The crystalline structure is an important part for LDH materials. It was reported that during the charging step, the surface of LDH materials is not the only part that participates, the entire crystalline structure is also involved via intercalation/de-intercalation of electrolyte ions; promoting the excellent energy storage capabilities of LDH materials [ 6 , 30 , 31 , 32 , 33 ]. Therefore, the LDH crystalline domain deserves attention.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 d shows the FTIR spectra for the LDH-100-1h, LDH-100-1h30, LDH-100-2h, LDH-150-1h, and LDH-200-1h electrodes. Generally, the nature of the LDH interlamellar also determines the electrochemical performance [ 30 , 41 ]. Since it was difficult to understand the nature of the interlamellar for all the as-fabricated binder-free LDH electrodes using XRD, the FTIR measurements for all the binder-free LDH electrodes were carried out.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations